The Plant Species Diversity of Lasitae Protected Nature Forest and Nearby Area, District of Barru, South Sulawesi - Rismita Sari; Inggit Pudji Astuti; Ratna Susandarini; Irwan Makmur (Journal of Tropical Biodiversity and Biotechnology, 2020)
An expedition to Lasitae Protected Forest in District of Barru, South Sulawesi was undertaken to collect living plants for Pucak Botanic Garden, South Sulawesi. The aims were to investigate the diversity of the plants and as a dedication to the Expedition of the Republic of Indonesia Corridor Sulawesi. Using an explorative method, we collected the plants and recorded all data in the field following the tracks assisted by the field guide. A total of 179 collection-numbers have been collected from this dry lowland forest including the data for the local names. Many potential and valuable plants occur in the forest, 13 plants were highlighted in this paper for its conservation status, the potentiality for various purposes or its uniqueness: Diospyros celebica Bakh. or streak ebony (Ebenaceae), Arenga pinnata (Wurmb.) Merr. (Arecaceae), Phyllanthus lamprophyllus Mull.Arg. (Phyllanthaceae), Cycas rumphii Miq. (Cycadaceae), Lagerstroemia speciosa (L.) Pers. (Lythraceae), Garcinia celebica L. (Clusiaceae), Nervilia aragoana Gaud. (Orchidaceae), Phalaenopsis amabilis (L.) Blume (Orchidaceae), Ophioglossum reticulatum L. (Ophioglossaceae), Tetracera scandens (L.) Merr. (Dilleniaceae), Derris trifoliata Lour., Phytocrene bracteata Wall. (Icacinaceae), and Dioscorea hispida Dennst. Buchanania arborescens (Blume) Blume and Ardisia elliptica Thunb. can easily be found and widely spread.